A REVIEW ARTICLE ON MADHU AND ITS PALLIATIVE MEASURE IN VRANAROPANA (International Journal of Food and Nutritional Sciences, 2022)
Since vedic kala Madhu is being used as ahara and aushadi.The literal meaning of Madhu is a substance which can be consumed as Leham(Jam like consistency). The description along with types and properties of Madhu is mentioned in various ayurvedic texts such as Charaka Samhita, Sushruta Samhita, Ashtanga Hridya, Bhava Prakasha, Yogaratnakara, and Harita Samhita. Madhu is Tri-doshhara, Chakshushya, Sangrahi, Vranaropaka in properties.Studies says that,the glycaemic index of Madhu is lower than sugar.Madhu posses mainly four activities which are anti-oxidant, anti-bacterial ,anti- viral and anti-inflammatory by which it helps in wound Care. In several ayurvedic treatments, it is also utilised as a natural preservative and sweetener. It is often used as a vehicle in combination with other medications to increase their efficacy or lessen their negative effects. Additionally, it is known to lessen the heightened kapha dosha. In this article we have tried to undersand role of Madhu as a palliative measure in Vranaropana.